Analisis Kepatuhan Minum Obat pada Pasien dengan Gangguan Jiwa di WIlayah Kerja Puskesmas Nanjungan Kabupaten Empat Lawang - Mulyani, Pipin; Wahyudi, Arie; Zaman, Chairil (Avicenna: Jurnal Ilmiah, 2025)
ABSTRACK Background: Mental disorders are psychological or behavioral patterns shown in individuals that cause distress, reduce the quality of life and dysfunction. This reflects psychological dysfunction, not as a result of social deviation or conflict with society. Methods: This study aims to determine the analysis of medication adherence in people with mental disorders (ODGJ) in the Nanjungan Health Center Work Area in 2025. This study design uses Cross Sectional, where the population in this study was 76 respondents, with a sample of 76. The sampling method in the study was total population sampling. This study was conducted on May 1 to June 1, 2025. Data collection and retrieval using a questionnaire. Results: The results of the statistical test analysis using the Chi-Square statistical test and logistic regression where the results showed a significant relationship (p value <0.05) for the media information variables (p value 0.02), access to health services (p value 0.02), availability of human resources (p value 0.01), income (p value 0.03), knowledge (p value 0.01), attitude (p value 0.03), family support (p value 0.00), and support from health workers (p value 0.00). From the results of the multivariate statistical test, the dominant factor in medication adherence is health information (p = 0.02; OR = 0.305). Conclusion: It is expected to improve the performance program of non-communicable diseases, especially medication adherence in ODGJ in the Nanjungan Health Center work area. Keywords: Compliance, Medication, ODGJ, Health Center